2022
DOI: 10.1111/jam.15342
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance and health benefits of soymilk fermented by lactic acid bacteria

Abstract: The growing interest of consumers towards nutritionally enriched, and health promoting foods, provoke interest in the eventual development of fermented functional foods. Soymilk is a growing trend that can serve as a low‐cost non‐dairy alternative with improved functional and nutritional properties. Soymilk acts as a good nutrition media for the growth and proliferation of the micro‐organism as well as for their bioactivities. The bioactive compounds produced by fermentation of soymilk with lactic acid bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 107 publications
1
26
0
Order By: Relevance
“…The pH values were significantly decreased after storage (table 1). Similar results found the pH value and viscosity were significantly decreased after storage [21], [20] also showed the same results that the increasing storage temperature and time can decreased the pH value…”
Section: Phsupporting
confidence: 74%
“…The pH values were significantly decreased after storage (table 1). Similar results found the pH value and viscosity were significantly decreased after storage [21], [20] also showed the same results that the increasing storage temperature and time can decreased the pH value…”
Section: Phsupporting
confidence: 74%
“…A recent study revealed soybean variety-dependent effects of Lactobacillus acidophilus and Lactobacillus casei fermentation on the isoflavones content and rheological properties of soymilk (Ahsan et al 2022). Other reports in animal models suggest that probiotic fermented soymilk can induce antihypertensive, antioxidant, antidiabetic, and hypocholesterolaemic effects and thus may have greater functional relevance (Kumari et al 2021). In this regard, a recent study has indicated that consumption of soymilkfermented with Lactobacillus delbrueckii subsp.…”
Section: Fermented Soymilkmentioning
confidence: 99%
“…Lactiplantibacillus plantarum is a versatile LAB strain which was extensively proposed as starter culture for plant-stuff fermentation. Foods fermented by L. plantarum have been proved with many functions including alleviating hyperlipidemia, hyperglycaemia and preventing obesity (Tiss et al, 2020;Kumari et al, 2021). However, the lipid regulation mechanism has not been sufficiently elucidated, especially based on the expression level of related key enzymes, hormones and transcriptional regulators involved in hepatic lipids metabolism, as well as the roles of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…The most concerned bioactive compound is the soy isoflavones, which play important roles in preventing CVD, and Lactic acid bacteria (LAB) fermentation could transform its glycoside precursor to aglycone with higher bioavailability (Du et al ., 2022). Furthermore, bioactive peptides and gamma‐aminobutyric acid were also notable nutraceuticals in fermented soymilk (FSM), which could reduce chronic diseases such as obesity, CVD and immune disorder (Kumari et al ., 2021). Therefore, FSM with LAB is a kind of prospective functional food in prevention and treatment of hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%